2022
DOI: 10.1002/adfm.202204974
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hollow‐Tube‐Biphasic‐Whisker‐Modified Calcium Phosphate Ceramics with Simultaneously Enhanced Mechanical Strength and Osteogenic Activity

Abstract: Due to the inherent brittleness and low mechanical strength, it is still a challenge for calcium phosphate (Ca-P) ceramics to be used in load-bearing bone defect repair. To achieve a good balance between mechanical strength and osteogenic activity, hollow-tube-whisker-modified biphasic calcium phosphate (BCP) ceramics (BCP-HW) are successfully fabricated by an in situ growth process in the present study. Compared to the initial BCP ceramics (BCP-C) and those with solid whiskers, BCP-HW exhibits larger specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have shown that micro-/nanotopography on Ca–P ceramic surfaces could modulate cell behavior. Compared with the microscale surface structure, the nanoscale surface structure of scaffolds can form more micropores and mesopores, thus promoting the deposition of proteins in these pores and providing abundant active sites for cell attachment. , …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that micro-/nanotopography on Ca–P ceramic surfaces could modulate cell behavior. Compared with the microscale surface structure, the nanoscale surface structure of scaffolds can form more micropores and mesopores, thus promoting the deposition of proteins in these pores and providing abundant active sites for cell attachment. , …”
Section: Discussionmentioning
confidence: 99%
“…Compared with the microscale surface structure, the nanoscale surface structure of scaffolds can form more micropores and mesopores, thus promoting the deposition of proteins in these pores and providing abundant active sites for cell attachment. 9,43 Moreover, cells are particularly sensitive to the microstructure of the scaffold surface. The adhesion of cells on the microscale surface is realized by the mutual aggregation of multiple receptor molecules, and the structural rearrangement can occur with the change of the microscale topological structure of the surface of the scaffold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that biphasic calcium phosphate (BCP) ceramics with whisker surface structures present favorable bone regeneration and bone defect repair performance. , Herein, we fabricated BCP ceramics with nanowhisker surface structure to investigate their large-segment bone defect repair performance in a rabbit tibial model. Then, the immunomodulatory features of nanowhisker structures and which of them influence osteogenesis and biomaterial resorption were further investigated.…”
Section: Introductionmentioning
confidence: 99%